Antarctic ice sheet response to sudden and sustained ice-shelf collapse (ABUMIP). Issue 260 (14th December 2020) - Sun, Sainan; Pattyn, Frank; Simon, Erika G.; Albrecht, Torsten; Cornford, Stephen; Calov, Reinhard; Dumas, Christophe; Gillet-Chaulet, Fabien; Goelzer, Heiko; Golledge, Nicholas R.; Greve, Ralf; Hoffman, Matthew J.; et al.
Abstract: Antarctica's ice shelves modulate the grounded ice flow, and weakening of ice shelves due to climate forcing will decrease their 'buttressing' effect, causing a response in the grounded ice. While the processes governing ice-shelf weakening are complex, uncertainties in the response of the grounded ice sheet are also difficult to assess. The Antarctic BUttressing Model Intercomparison Project (ABUMIP) compares ice-sheet model responses to decrease in buttressing by investigating the 'end-member' scenario of total and sustained loss of ice shelves. Although unrealistic, this scenario enables gauging the sensitivity of an ensemble of 15 ice-sheet models to a total loss of buttressing, hence exhibiting the full potential of marine ice-sheet instability. All models predict that this scenario leads to multi-metre (1–12 m) sea-level rise over 500 years from present day. West Antarctic ice sheet collapse alone leads to a 1.91–5.08 m sea-level rise due to the marine ice-sheet instability. Mass loss rates are a strong function of the sliding/friction law, with plastic laws cause a further destabilization of the Aurora and Wilkes Subglacial Basins, East Antarctica. Improvements to marine ice-sheet models have greatly reduced variability between modelled ice-sheet responses to extreme ice-shelf loss, e.g. compared to the SeaRISE assessments.